Pengaruh Country Of Origin Terhadap Brand Image dan Purchase Decision Kosmetik Merek BLP Beauty Di Kota Banjarmasin - Faradella Zsella Zeverina; Hairudinor Hairudinor (Universitas Lambung Mangkurat, 2023)
In the current era of globalization and rapid technological advances, the business world is growing rapidly and business competition is increasingly competitive. Currently, Indonesia is being hit by the Korean Wave phenomenon which has resulted in many people preferring products originating from South Korea, especially cosmetic products. origin for Indonesian cosmetic products and pay attention to brand image. This study aims to determine and analyze the effect of Country of Origin on Brand Image and Purchase Decision of BLP Beauty Cosmetics in Banjarmasin City. The sample in this study amounted to 100 respondents This research uses a quantitative approach with causal explanatory research. This study uses PLS as a data analysis technique with Smart PLS.The results of this study indicate that the country of origin has a significant effect on purchase decisions through brand image, while the country of origin has no significant effect on purchase decisions on BLP Beauty brand cosmetic products in Banjarmasin City Keywords: Country of Origin, Brand Image, Purchase Decision, Cosmetic